Analysis of Students' Mathematical Understanding using the Pirie-Kieren Lens - Zawawi, Irwani; Huda, Syaiful; Afriani, Irma Surya (Jurnal Pendidikan MIPA, 2023)
Creating a learning environment that supports students' understanding is an important notion in mathematics education (Carpenter & Lehrer, 1999). In this case, it is necessary to have a flow in the learning process. Learning trajectory will help teachers apply models, teaching material strategies and appropriate assessments according to students' thinking stages. The flow of student learning in the development of symbols and their meaning in mathematics can be done through technology and information (Bakker et al., 2003). The purpose of this study is to analyze the understanding of mathematical concepts in high school students using the Pirie-Kieren theory lens. Based on the results of the analysis of student worksheets for groups with visual, auditory, and kinesthetic learning styles, they have fulfilled the layer of Piere-Kieren understanding up to the stage/organizing layer. The difference in the results of the worksheets of the students in the three groups of learning styles can be seen in their process of finding ways to arrange the candies/boxes equally.Creating a learning environment that supports students' understanding is an important notion in mathematics education (Carpenter & Lehrer, 1999). In this case, it is necessary to have a flow in the learning process. Learning trajectory will help teachers apply models, teaching material strategies and appropriate assessments according to students' thinking stages. The flow of student learning in the development of symbols and their meaning in mathematics can be done through technology and information (Bakker et al., 2003). The purpose of this study is to analyze the understanding of mathematical concepts in high school students using the Pirie-Kieren theory lens. Based on the results of the analysis of student worksheets for groups with visual, auditory, and kinesthetic learning styles, they have fulfilled the layer of Piere-Kieren understanding up to the stage/organizing layer. The difference in the results of the worksheets of the students in the three groups of learning styles can be seen in their process of finding ways to arrange the candies/boxes equally. Keywords: mathematics learning, Piere-Kieren theory, high school students. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp442-452